Antifibrotic Activity of Human Placental Amnion Membrane-Derived CD34+ Mesenchymal Stem/Progenitor Cell Transplantation in Mice With Thioacetamide-Induced Liver Injury. (12th July 2016) - Lee, Po-Huang; Tu, Chi-Tang; Hsiao, Chih-Chiang; Tsai, Ming-Song; Ho, Cheng-Maw; Cheng, Nai-Chen; Hung, Tzu-Min; Shih, Daniel Tzu-bi
Abstract : This study aimed to evaluate the therapeutic effect of mesenchymal stromal cell (MSC)-based cell transplantation as an alternative treatment for liver fibrosis. When injected into the spleen of thioacetamide-injured mice, human placental amnion membrane-derived MSCs can engraft into the injury site, ameliorate liver fibrosis, and restore liver function, Abstract: Liver fibrosis represents the end stage of chronic liver inflammatory diseases and is defined by the abnormal accumulation of extracellular matrix in the liver. Advanced liver fibrosis results in cirrhosis, liver failure, and portal hypertension. Liver transplantation has been the most effective treatment for these diseases, but the procedure is limited by the shortage of suitable donors. Mesenchymal stromal cells (MSCs) have shown great potential in the treatment of chronic inflammatory diseases associated with fibrosis. This study aimed to evaluate the therapeutic effect of MSC-based cell transplantation as an alternative treatment for liver fibrosis. A CD34-positive subpopulation of human placental amnion membrane-derived stem/progenitor cells (CD34 + AMSPCs) was isolated through the depletion of CD34-negative stromal fibroblasts (CD34 − AMSFCs) facilitated by CD34 fluorescence-activated cell sorting, enriched and expanded ex vivo. These cells express pluripotency markers and demonstrate multidirectional differentiation potentials. Comparative analysis was made between CD34 + AMSPCs and CD34 − AMSFCs in terms of the expressions of stemness surface markers, embryonic surface antigens, and multilineage differentiation potentials. A mouse model of liver fibrosis was established by thioacetamide (TAA) administration. When injected into the spleen of TAA-injured mice, human placental amnion membrane-derived MSCs (hAM-MSCs) can engraft into the injury site, ameliorate liver fibrosis, and restore liver function, as shown by pathological and blood biochemical analysis and downregulated gene expressions associated with liver damage. CD34 + AMSPCs represent a more primitive subset of hAM-MSCs and could be a suitable candidate with a potentially better safety profile for cell-based therapy in treatment of liver diseases associated with fibrosis. Significance: In this study, a CD34 + subpopulation of stem/progenitor cells derived from neonatal placental amnion membrane, denoted as CD34 + AMSPCs, were identified, enriched, and characterized. These cells are highly proliferative, express mesenchymal stromal cells and pluripotent stem cell markers, and demonstrate multidirectional differentiation potentials, indicating their promising application in clinical regenerative therapies. CD34 + AMSPC transplantation ameliorated liver fibrosis in mice with drug-induced liver injury. These cells represent a potential therapeutic agent for treating liver diseases associated with fibrosis.